Redox‐Active Hybrid Polyoxometalate‐Stabilised Gold Nanoparticles. Issue 34 (29th June 2020) - Martin, Carmen; Kastner, Katharina; Cameron, Jamie M.; Hampson, Elizabeth; Alves Fernandes, Jesum; Gibson, Emma K.; Walsh, Darren A.; Sans, Victor; Newton, Graham N.
Abstract: We report the design and preparation of multifunctional hybrid nanomaterials through the stabilization of gold nanoparticles with thiol‐functionalised hybrid organic–inorganic polyoxometalates (POMs). The covalent attachment of the hybrid POM forms new nanocomposites that are stable at temperatures and pH values which destroy analogous electrostatically functionalised nanocomposites. Photoelectrochemical analysis revealed the unique photochemical and redox properties of these systems. Abstract : Handy hybrids : A material based on gold nanoparticles stabilized by organic–inorganic hybrid polyoxometalates is described (see picture). The new nanomaterial exhibits unprecedented stability and photoactivity under visible light and can be reversibly reduced and oxidized at electrode surfaces, making it very promising for future photonic and electrochemical systems.